DES science portal: Creating science-ready catalogs - Fausti Neto, A.; da Costa, L. N.; Carnero, A.; Gschwend, J.; Ogando, R. L.C.; Sobreira, F.; Maia, M. A.G.; Santiago, B. X.; Rosenfeld, R. [UNESP]; Singulani, C.; Adean, C.; Nunes, L. D.P.; et al. (Elsevier, 2018)
We present a novel approach for creating science-ready catalogs through a software infrastructure developed for the Dark Energy Survey (DES). We integrate the data products released by the DES Data Management and additional products created by the DES collaboration in an environment known as DES Science Portal. Each step involved in the creation of a science-ready catalog is recorded in a relational database and can be recovered at any time. We describe how the DES Science Portal automates the creation and characterization of lightweight catalogs for DES Year 1 Annual Release, and show its flexibility in creating multiple catalogs with different inputs and configurations. Finally, we discuss the advantages of this infrastructure for large surveys such as DES and the Large Synoptic Survey Telescope. The capability of creating science-ready catalogs efficiently and with full control of the inputs and configurations used is an important asset for supporting science analysis using data from large astronomical surveys.
Keywords: Astronomical databases; Catalogs; Data analysis; Surveys—methods